Prevalence of dementia, cognitive status and associated risk factors among elderly of Zhejiang province, China in 2014 - Yang, Li; Jin, Xiaoqing; Yan, Jing; Jin, Yu; Yu, Wei; Wu, Haibin; Xu, Shanhu (Age and ageing, 2016)
the prevalence of dementia in China has risen dramatically in recent decades, but it is not well understood the status in the elderly population in Zhejiang province, eastern China. a cross-sectional survey was conducted in four communities across 12 counties in Zhejiang province from May to November 2014. Recruitment included 2,015 subjects aged 65 or older. Trained assessors performed assessments and interviews and collected information. Dementia was diagnosed according to the NIA-AA criteria in 2011. the age-gender-standardised prevalence rates of dementia, Alzheimer's disease and vascular dementia were 13.0, 6.9 and 0.5%, respectively. There were significant increasing trends of rates over ages. Elderly, low educational level, heavy smoking, heavy alcohol consumption, diabetes and stroke were associated with dementia; tea consumption was associated with low prevalence of Alzheimer's disease and severe cognitive impairment. dementia and cognitive impairment were relatively high among the elderly in Zhejiang province; more attention and population-based strategies are needed.